(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Nowadays most of known organizations are obsessed with product and service quality since customer’s orientation has been shifted from product & service price to its quality. Thus, most of the organizations are willing to adopt the TQM concept and processes in order to achieve their objectives, meet their customer’s expectations and attain competitive advantage. TQM is a management philosophy that seeks to integrate all organizational functions to focus on meeting customer needs and organizational objectives. In this paper we will highlight the organization role and the support of the employees to reach the maximum degree of the TQM. We will also describe some Asian TQM case studies in order to summarize the most important factors for successful TQM implementation.